Tumour cells express functional lymphatic endothelium-specific hyaluronan receptor in vitro and in vivo: Lymphatic mimicry promotes oral oncogenesis? - Karinen, Sini (Oncogenesis, 2021)
Lymphatic metastasis represents the main route of tumour cell dissemination in oral squamous cell carcinoma (OSCC). Yet, there are no FDA-approved therapeutics targeting cancer-related lymphangiogenesis to date. The lymphatic vessel endothelial hyaluronic acid receptor 1 (LYVE-1), a specific lymphatic marker, is associated with poor survival in OSCC patients. In this study, we present a potential novel mechanism of lymphatic metastasis in OSCC—lymphatic mimicry (LM), a process whereby tumour cells form cytokeratin(+)/LYVE-1(+), but podoplanin-negative, mosaic endothelial-like vessels. LM was detected in one-third (20/57; 35.08%) of randomly selected OSCC patients. The LM-positive patients had shorter overall survival (OS) compared to LM-negative group albeit not statistically significant. Highly-metastatic tumour cells formed distinct LM structures in vitro and in vivo. Importantly, the siRNA-mediated knockdown of LYVE-1 not only impaired tumour cell migration but also blunted their capacity to form LM-vessels in vitro and reduced tumour metastasis in vivo. Together, our findings uncovered, to our knowledge, a previously unknown expression and function of LYVE-1 in OSCC, whereby tumour cells could induce LM formation and promote lymphatic metastasis. Finally, more detailed studies on LM are warranted to better define this phenomenon in the future. These studies could benefit the development of targeted therapeutics for blocking tumour-related lymphangiogenesis.